2021
DOI: 10.3390/su13147984
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Socio-Economic Problems in Crisis Areas through Revitalization of Cittaslow Towns. Evidence from North-East Poland

Abstract: The revitalization of small towns is connected with an attempt to find multidirectional solutions to numerous social, economic and spatial problems. It is possible to remove degraded areas and areas with a high risk of social exclusion through coordinated and skillfully planned activities consisting of corrective interventions within these areas and, indirectly, in the whole structure of a small town. There are many studies on improving the quality of life of inhabitants at risk of exclusion in large cities. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…The results of the study support the study of Sendi and Kerbler [19], who found that the creation of public spaces had a positive impact on the social connections of the residents. The results obtained and the example of the revitalization of the Žirm ūnai triangle analyzed are in line with the study of Zielinska-Szczepkowska, Jaszczak, and Žukovskis [59], who analyzed revitalization solutions in small towns that improved the sense of security, but the revitalization of the Žirm ūnai triangle did not lead to the creation of any new jobs. This study extends the study of Dsoiza et al [11] by providing an example of revitalization with clearly identified outcomes that could motivate residents to contribute to revitalization.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results of the study support the study of Sendi and Kerbler [19], who found that the creation of public spaces had a positive impact on the social connections of the residents. The results obtained and the example of the revitalization of the Žirm ūnai triangle analyzed are in line with the study of Zielinska-Szczepkowska, Jaszczak, and Žukovskis [59], who analyzed revitalization solutions in small towns that improved the sense of security, but the revitalization of the Žirm ūnai triangle did not lead to the creation of any new jobs. This study extends the study of Dsoiza et al [11] by providing an example of revitalization with clearly identified outcomes that could motivate residents to contribute to revitalization.…”
Section: Discussionsupporting
confidence: 85%
“…Revitalization in small towns had included the creation of public spaces, local frontages, social gathering places, and the renovation of natural places such as lakes and riversides. These solutions helped to create social links, as people become involved in organized events, met new people, and crime rates also decreased [59]. According to recent research, community revitalization projects that refurbished public places fostered social interactions, made it easier for newcomers to settle in, boosted neighborhood satisfaction, and enhanced their inhabitants' psychological well-being [60].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The social function involves the improvement of the conditions and quality of life of residents of rural areas (Krzyminiewska, 2000;Majewski & Perepeczko, 2001;Fedyszak-Radziejowska, 2016), development of the social infrastructure (Kalinowski, 2003), development of non-material cultural heritage (Jalinik, 2006), revitalisation programmes activating the society (Zielińska-Szczepkowska et al, 2021;Sykała, 2019), and activities aimed at shaping attitudes from reactive (yielding to events, lack of engagement) towards proactive (designating and implementing goals) (Chyłek, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies of revitalization cases are numerous [26][27][28] because they are very relevant in the modern world. The problem of revitalization is very relevant in former socialist countries because of specific conditions of their development after World War Two [29][30][31].…”
Section: Introductionmentioning
confidence: 99%